2010
DOI: 10.1016/j.actbio.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel thermosensitive polymer with pH-dependent degradation for drug delivery

Abstract: A class of thermosensitive biodegradable multiblock copolymers with acid-labile acetal linkages were synthesized from Pluronic® triblock copolymers (Pluronic® P85 and P104) and di-(ethylene glycol) divinyl ether. The novel polymers were engineered to form thermogels at body temperature and degrade in acidic environment. The Pluronic®-based acid-labile polymers were characterized using nuclear magnetic resonance, gel permeation chromatography and differential scanning calorimetry. In vitro biocompatibility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 43 publications
2
72
0
Order By: Relevance
“…These complexes displayed enhanced intracellular uptake and silencing effect of siRNA in cancer cells under applied magnetic force. Pluronic, an amphiphilic tri-block copolymer consisting of poly-(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), is wellknown for its biocompatibility (Kwon et al, 2009;Namgung et al, 2009b;Garripelli et al, 2010). Pluronic derivatives and oleic acid-coated iron oxide nanocrystals in an organic solvent were ultrasonically emulsified in an aqueous PEI solution.…”
Section: Polyethyleniminementioning
confidence: 99%
“…These complexes displayed enhanced intracellular uptake and silencing effect of siRNA in cancer cells under applied magnetic force. Pluronic, an amphiphilic tri-block copolymer consisting of poly-(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), is wellknown for its biocompatibility (Kwon et al, 2009;Namgung et al, 2009b;Garripelli et al, 2010). Pluronic derivatives and oleic acid-coated iron oxide nanocrystals in an organic solvent were ultrasonically emulsified in an aqueous PEI solution.…”
Section: Polyethyleniminementioning
confidence: 99%
“…19 Accordingly, thermo-and pH-responsive PNIPAM-based copolymers for drug delivery systems have been previously reported. [20][21][22][23][24][25] Furthermore, poly acrylic acid (PAA, Carbopol, polycarbophil) is deemed to be a polymer with bioadhesive and pH-dependence properties, even though it is difficult to maintain its effectiveness in GI tract. Using polyglycerol esters of fatty acids and PAA derivatives, mucoadhesive microparticles have been prepared and examined as in vivo and invitro in rats showing prolonged gastrointestinal residence.…”
Section: Introductionmentioning
confidence: 99%
“…22 It is known that the release of acidic degradation by-products from some degradable polymers could lead to inflammatory responses in vivo, and many methods have been tried to control the pH decrease during the degradation of these polymers. 23,24 In this study, it was found that there was gradually a decrease of pH in the solution containing WP (from 7.40 to 7.10), indicating that some acidic products (amino acids) might be produced from WP degradation during the soaking process. However, the pH for MWC scaffolds showed a slight increase from the initial value of 7.40 to 7.76 during the soaking process.…”
mentioning
confidence: 95%